The Role of Wnt/β-Catenin Pathway Mediators in Aortic Valve Stenosis - Khan, Kashif; Yu, Bin; Kiwan, Chrystina; Shalal, Yousif; Filimon, Sabin; Cipro, Megan; Shum-Tim, Dominique; Cecere, Renzo; Schwertani, Adel (Frontiers in Cell and Developmental Biology, 2020)
Aortic valve stenosis (AVS) is a prevailing and life-threatening cardiovascular disease in adults over 75 years of age. However, the molecular mechanisms governing the pathogenesis of AVS are yet to be fully unraveled. With accumulating evidence that Wnt signaling plays a key role in the development of AVS, the involvement of intracellular Wnt molecules has become an integral study target in AVS pathogenesis. Thus, we hypothesized that the Wnt/β-catenin pathway Wnt intracellular mediators, SFRP2, DVL2, GSK3β and β-catenin are dysregulated in patients with AVS. Using immunohistochemistry, Real-Time qPCR and Western blotting, we investigated the presence of SFRP2, GSK-3β, DVL2 and β-catenin in normal and stenotic human aortic valves. Markedly higher mRNA and protein expression of GSK-3β, DVL2, β-catenin and SFRP2 were found in stenotic aortic valves. This was further corroborated by observation of their abundant immunostaining, which displayed strong immunoreactivity in diseased aortic valves. Proteomic analyses of selective GSK3b inhibition in calcifying human aortic valve interstitial cells (HAVICs) revealed enrichment of proteins involved organophosphate metabolism, while reducing the activation of pathogenic biomolecular processes. Lastly, use of the potent calcification inhibitor, Fetuin A, in calcifying HAVICs significantly reduced the expression of Wnt signaling genes Wnt3a, Wnt5a, Wnt5b and Wnt11. The current findings of altered expression of canonical Wnt signaling in AVS suggest a possible role for regulatory Wnts in AVS. Hence, future studies focused on targeting these molecules are warranted to underline their role in the pathogenesis of the disease.